Pengaruh Effleurage Massage Dengan Minyak ZaitunTerhadap Risiko Terjadinya Decubitus Pada Pasien Stroke Di Panti Sosial Bina Daksa Budi Bhakti 2 Jakarta Barat - Sari, Novita; Mataputun, Donny Richard (Sekolah Tinggi Ilmu Kesehatan Sumber Waras, 2026)
Background: Stroke is one of the main causes of disability which is often accompanied by limited mobility, thus increasing the risk of decubitus. Decubitus can prolong the treatment period if not prevented optimally. One of the nonpharmacological nursing interventions that can be used to prevent decubitus is Effleurage massage with olive oil. Objective: This study aims to determine the effect of Effleurage massage with olive oil on the risk of decubitus in stroke patients at the Bina Daksa Budi Bhakti 2 Social Home, West Jakarta Method: This study uses a quantitative method with a pre-experimental design through a one group pretest–posttest design. The population in this study is stroke patients at the Bina Daksa Budi Bhakti 2 Social Home, West Jakarta, with a sample of 5 respondents selected using purposive sampling techniques. Data collection was carried out by assessing the risk of decubitus using the Braden Scale before and after the administration of Effleurage massage with olive oil. Results: The results showed that before the intervention, Braden's average score was 12.00, with most respondents in the moderate to severe risk category. After being given Effleurage massage with olive oil, the average value of Braden's score increased to 17.40, and all respondents moved to the mild risk category. Result Paired Samples T-Test p-value 0,000 (p<0,05). Conclusion: Effleurage massage with olive oil has a positive effect on reducing the risk of decubitus in stroke patients.